Spatiotemporal Characteristics of and Factors Influencing CO2 Concentration During 2010–2023 in China - Jiayi Zou; Huaixu Jiang; Tianshun Yang; Liqing Wu; Qi Zhang; Jianjun Xu (Remote Sensing)
Human activities at unprecedented levels have exacerbated the greenhouse effect and escalated the frequency of extreme weather. In response, the Chinese government has pledged to reach “carbon peak” by 2030 and achieve “carbon neutrality” by 2060. Leveraging the GOSAT L3 and L4B CO2 datasets, this study investigated the spatiotemporal and vertical characteristics of atmospheric carbon dioxide (CO2) concentration across China, alongside quantifying the relative importance of key influencing factors. The results show that there is a distinct regional disparity in CO2 column concentration, with eastern China having a higher concentration level (406.85 × 10−6) than the western regions (400.92 × 10−6). Vertically, the concentration of CO2 (390–420 × 10−6) reaches its peak at the near-surface layer (975 hPa) and then decreases with increasing altitude. High values of CO2 levels in the mid-lower layer are concentrated in eastern China, while those in the upper layer are mainly located in southern China. In addition, CO2 concentration shows seasonal variations, with the highest concentration occurring in spring (406.39 × 10−6) and the lowest in summer. Biospheric emissions and fossil fuel combustion emerge as the two most significant factors affecting CO2 variation, with relative importance of 24% and 22%, respectively.